2016
DOI: 10.1002/2015ms000529
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the MJO in a cloud‐resolving model with parameterized large‐scale dynamics: Vertical structure, radiation, and horizontal advection of dry air

Abstract: Two Madden-Julian Oscillation (MJO) events, observed during October and November 2011 in the equatorial Indian Ocean during the DYNAMO field campaign, are simulated in a limited-area cloudresolving model using parameterized large-scale dynamics. Three parameterizations of large-scale dynamics-the conventional weak temperature gradient (WTG) approximation, vertical mode-based spectral WTG (SWTG), and damped gravity wave coupling (DGW)-are employed. A number of changes to the implementation of the large-scale pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 80 publications
(170 reference statements)
1
71
0
Order By: Relevance
“…Globally, a large number of the most intense precipitation events occur in the subtropical belt during summer [Zipser et al, 2006;Cecil and Blankenship, 2012], likely results of interactions between extratropical dynamics with sufficient moisture supply from the tropics. Applying the CQG method of this study to events in other regions, e.g., Texas [e.g., Simon Wang et al, 2015] or the Middle East [e.g., de Vries et al, 2013], may be useful in identifying the most important physical factors leading to extreme precipitation events in these different regions.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, a large number of the most intense precipitation events occur in the subtropical belt during summer [Zipser et al, 2006;Cecil and Blankenship, 2012], likely results of interactions between extratropical dynamics with sufficient moisture supply from the tropics. Applying the CQG method of this study to events in other regions, e.g., Texas [e.g., Simon Wang et al, 2015] or the Middle East [e.g., de Vries et al, 2013], may be useful in identifying the most important physical factors leading to extreme precipitation events in these different regions.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This modeling framework extends the notion of ''parameterization of large-scale dynamics'' previously applied in the tropics-including the weak-temperature-gradient method [e.g., Sobel and Bretherton, 2000;Raymond and Zeng, 2005;Daleu et al, 2015], the damped-gravity-wave method [e.g., Kuang, 2008;Blossey et al, 2009;Romps, 2012;Daleu et al, 2015], and related others [e.g., Mapes, 2004;Bergman and Sardeshmukh, 2004]-to parameterize large-scale vertical motion. These methods allow attribution of precipitation to environmental factors such as the sea surface temperature (SST) or the large-scale tropospheric temperature profile, and have been used to aid understanding of a variety of phenomena in the tropics [e.g., Chiang and Sobel, 2002;Wang et al, 2013Wang et al, , 2015Nie and Sobel, 2015;Sessions et al, 2015]. In the extratropics, quasi-balanced dry adiabatic PV dynamics, captured in an approximate way by the QG system [e.g., Charney, 1948;Phillips, 1951;Hoskins et al, 1985] plays a larger role in inducing large-scale vertical motion than it does in the tropics.…”
Section: Introductionmentioning
confidence: 99%
“…They identified significant spread in radiative fluxes and stratiform cloud coverage when different microphysical schemes are used. Wang et al () further demonstrated important roles of horizontal advection of moisture and radiative feedback in driving the MJO in their WRF simulations with parameterized large‐scale dynamics. These studies used the large‐scale forcing approach because it guarantees accurate simulations of domain‐mean moisture budget and surface precipitation.…”
Section: Introductionmentioning
confidence: 94%
“…Strong cloud‐radiative feedback in the Indian Ocean [e.g., Lin et al ., ] is found to play an important role in driving large variations in the surface fluxes, moisture advection, and moist static energy [e.g., Maloney et al ., ; Sobel et al ., ; Sobel and Maloney , ; Sobel et al ., ; Pritchard and Bretherton , ; Johnson et al ., ] for the MJO events observed during the Dynamics of the Madden‐Julian Oscillation (DYNAMO) field campaign [ Yoneyama et al ., ]. Importance of radiation [ Wang et al ., ] for the MJO events and also its interactions with cloud for maintaining the vertical structure of large‐scale velocity [ Wang et al ., ] is also demonstrated using cloud‐resolving model.…”
Section: Introductionmentioning
confidence: 99%